2017
DOI: 10.1039/c6cp08356k
|View full text |Cite
|
Sign up to set email alerts
|

Selective-releasing-affected lubricant mechanism of a self-assembled MoS2/Mo–S–C nanoperiod multilayer film sliding in diverse atmospheres

Abstract: A self-assembled MoS/Mo-S-C multilayer film prepared by r.f. co-sputtering of MoS and graphite targets was tribotested in diverse sliding atmospheres, and the lubricant mechanism and its correlations to the selective releasing behavior of non-lubricant component were analyzed in detail. Based on the analysis of composition and structural transformation of transferred materials by Raman and HRTEM characterizations, selective releasing behavior according to the sliding atmospheres were found to be particularly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…9d one can distinguish the long (> tens of nm) WS 2 platelets formed in the tribofilm from the randomized short WS 2 platelets (5 nm) in the raw coating. Most interestingly, perfectly aligned lamellae, with d = 0.63 nm characteristic of (002) WS 2 plane, extend up to > 60 nm, which is much thicker than reported in earlier work (several nm) [37,54]. Fig.…”
Section: Characterization Of the Ws 2 Tribofilmmentioning
confidence: 53%
“…9d one can distinguish the long (> tens of nm) WS 2 platelets formed in the tribofilm from the randomized short WS 2 platelets (5 nm) in the raw coating. Most interestingly, perfectly aligned lamellae, with d = 0.63 nm characteristic of (002) WS 2 plane, extend up to > 60 nm, which is much thicker than reported in earlier work (several nm) [37,54]. Fig.…”
Section: Characterization Of the Ws 2 Tribofilmmentioning
confidence: 53%
“…4a confirms thick (002)-orientated WS 2 layers are transferred onto the counterpart ball. Previous study [4,10,11] reported that amorphous TMDs crystallize initially from the bottom of the wear track and become mostly ordered at the outmost tribofilm. On the contrary, Fig.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…It is in strong contrast to Figure 4(b) where WS 2 platelets are apparently aligned and connected over the interface, suggesting the potential of such patches to heal irregular notches/cracks. WS 2 platelets are also elongated and densified near the interface, as illustrated by Figure 4(c), due to the crystallization of WS 2 even from an amorphous state under cyclic loading [21]. HR-TEM observations in Figure S6 show that the oxidation of WS 2 into WO 3 may locally block or diverge the perfect alignment of WS 2 basal plane.…”
Section: Resultsmentioning
confidence: 93%